Impact Twitter (X) Sentiment to Abnormal Return IDX30 Stocks - Elli, Farras Ghazyafi (Quantitative Economics and Management Studies, 2025)
Abnormal return serves as evidence of investors’ irrational behavior in response to unexpected or dramatic information. Such irrational behavior can be reflected in sentiments expressed on social media platforms such as Twitter (X). Recently, we revealed that sentiments expressed on Twitter (X) could influence stocks return rate. In this study, to analyze the effect of sentiment on Twitter (X) on stock price returns, we observed Twitter (X) sentiment and abnormal returns on IDX30 stocks. This research employs secondary data comprising 23,406 tweets related to 30 IDX30-listed stocks during the observation period fom July 2023 to December 2023. The secondary data were processed into sentiment scores and analyzed using Granger causality to examine the predictive ability of sentiment polarity on abnormal returns of IDX30 stocks. The results show that 5 out of 8 listed companies, that have causal relationship betweet positive sentiment and abnormal return, shows positive evaluation Granger Cause abnormal return. It indicated that positive sentiment could predict the abnormal return. Otherwise, 4 out 11 listed companies, that have causal relationship between negative sentiment and abnormal return, shows negative evaluation Granger Cause abnormal return. It indicated that negative sentiment is driven by abnormal returns. This research contributes to a better understanding of the Efficient Market Hypothesis in the Indonesia Stock Exchange and provides recommendation for improving the prediction of abnormal returns in the market through sentiment polarity analysis.